AKTIVITAS OFF-BALANCE SHEET, RISIKO DAN KINERJA BANK - , Purwo Adi Wibowo, Dr. Suad Husnan, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Based on empirical perspective, the motivation of study is based the average growth of OBS activities that exceed the average growth of total assets, equity, and the proportion of growth comparable with the average growth of loans. Meanwhile based on theoretical perspectives, there is scarcity of research theme about off-balance sheet activity especially in developing country